Anti-inflammatory treatment for major depressive disorder: implications for patients with an elevated immune profile and non-responders to standard antidepressant therapy. (September 2017) - Kopschina Feltes, Paula; Doorduin, Janine; Klein, Hans C; Juárez-Orozco, Luis Eduardo; Dierckx, Rudi AJO; Moriguchi-Jeckel, Cristina M; de Vries, Erik FJ
Major depressive disorder (MDD) is a prevalent and disabling psychiatric disease with rates of non-responsiveness to antidepressants ranging from 30–50%. Historically, the monoamine depletion hypothesis has dominated the view on the pathophysiology of depression. However, the lack of responsiveness to antidepressants and treatment resistance suggests that additional mechanisms might play a role. Evidence has shown that a subgroup of depressive patients may have an underlying immune deregulation that could explain the lack of therapeutic benefit from antidepressants. Stimuli like inflammation and infection can trigger the activation of microglia to release pro-inflammatory cytokines, acting on two main pathways: (1) activation of the hypothalamic–pituitary adrenal axis, generating an imbalance in the serotonergic and noradrenergic circuits; (2) increased activity of the enzyme indoleamine-2, 3-dioxygenase, resulting in depletion of serotonin levels and the production of quinolinic acid. If this hypothesis is proven true, the subgroup of MDD patients with increased levels of pro-inflammatory cytokines, mainly IL-6, TNF-α and IL-1β, might benefit from an anti-inflammatory intervention. Here, we discuss the pre-clinical and clinical studies that have provided support for treatment with non-steroidal anti-inflammatory drugs in depressed patients with inflammatory comorbidities or an elevated immune profile, as well as evidences for anti-inflammatory properties of standard antidepressants.